2019
DOI: 10.2196/13161
|View full text |Cite
|
Sign up to set email alerts
|

Time to Treatment and In-Hospital Major Adverse Cardiac Events Among Patients With ST-Segment Elevation Myocardial Infarction Who Underwent Primary Percutaneous Coronary Intervention (PCI) According to the 24/7 Primary PCI Service Registry in Iran: Protocol for a Cross-Sectional Study

Abstract: BackgroundPatients with ST-segment elevation myocardial infarction (STEMI) experience major adverse cardiac events (MACEs) following primary percutaneous coronary intervention (PCI). Although the relationship between time to treatment (eg, door-to-balloon time, symptom onset-to-balloon time, and symptom onset-to-door time) and 1-month all-cause mortality was assessed previously, its relationship with in-hospital MACEs and the effect of some clinical characteristics on this relationship were not considered. Fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
(36 reference statements)
0
10
1
Order By: Relevance
“…We conducted an observational study according to the 24/7 primary PCI service registry of THC in Iran. Details of the study design and setting have been published previously [ 26 ]. The study protocol was approved by the institutional review board and research ethics committee of Tehran University of Medical Sciences.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We conducted an observational study according to the 24/7 primary PCI service registry of THC in Iran. Details of the study design and setting have been published previously [ 26 ]. The study protocol was approved by the institutional review board and research ethics committee of Tehran University of Medical Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion criteria for this study were age older than 18 years, confirmed diagnosis of STEMI, and primary PCI through a standard technique without bolus administration of fibrinolytic agents in the catheterization laboratory of THC. Those with incomplete data regarding one of the time to treatment variables (eg, symptom-to-door time, door-to-balloon time, and symptom-to-balloon time) and the study outcome (ie, in-hospital MACCEs) were excluded from the analysis [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations